Assessment of In Vitro Bioaccessibility of Polyphenols from Annurca, Limoncella, Red Delicious, and Golden Delicious Apples Using a Sequential Enzymatic Digestion Model - Giulia Graziani; Anna Gaspari; Claudio Di Vaio; Aurora Cirillo; Carolina Liana Ronca; Michela Grosso; Alberto Ritieni (Antioxidants, 2021)
Four different varieties of apples have been considered (Limoncella, Annurca, Red Delicious, and Golden Delicious) to estimate the extent of colon polyphenolics release after in vitro sequential enzyme digestion. Since several studies report a positive effect of apple polyphenols in colonic damage, we found of interest to investigate the colon release of polyphenols in different varieties of apples in order to assess their prevention of colonic damage. UHPLC-HRMS analysis and antioxidant activity (ABTS, DPPH, and FRAP assays) were carried out on the apple extracts (peel, flesh, and whole fruit) obtained from not digested samples and on bioaccessible fractions (duodenal and colon bioaccessible fractions) after in vitro digestion. Polyphenolic content and antioxidant activities were found to vary significantly among the tested cultivars with Limoncella showing the highest polyphenol content accompanied by an excellent antioxidant activity in both flesh and whole fruit. The overall trend of soluble antioxidant capacity from the soluble duodenal phase (SDP) and soluble colonic phase (SCP) followed the concentrations of flavanols, procyandinis, and hydroxycinnamic acids under the same digestive steps. Our results highlighted that on average 64.2% of the total soluble antioxidant activity was released in the SCP with Limoncella exhibiting the highest values (82.31, 70.05, and 65.5%, respectively for whole fruit, flesh, and peel). This result suggested that enzymatic treatment with pronase E and viscozyme L, to reproduce biochemical conditions occurring in the colon, is effective for breaking the dietary fiber-polyphenols interactions and for the release of polyphenols which can exercise their beneficial effects in the colon. The beneficial effects related to the Limoncella consumption could thus be of potential great relevance to counteract the adverse effects of pro-oxidant and inflammatory processes on intestinal cells.